2006
DOI: 10.2307/40264305
|View full text |Cite
|
Sign up to set email alerts
|

Language Learners' Perceptions of Accent

Abstract: This study analyzed the accent perceptions of a group of 37 English language learners and 10 American undergraduate students. Each subject listened to a one-minute passage read by four speakers with different accents of English: General American, British English, Chinese English, and Mexican English. Participants then attempted to identify the different accents and stated their preferences and opinions about each. They also provided background information, including reasons for studying English and pronunciati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(79 citation statements)
references
References 21 publications
5
64
1
Order By: Relevance
“…These findings indicate that the participants wish to sound more native-like when speaking English. The results are consistent with the findings of Scales et al (2006) study. They found that the majority of the non-native speakers in their study stated that they tried to sound native-like.…”
Section: Questionnaire and Interview: Target Language Vs Mother Tongsupporting
confidence: 83%
See 2 more Smart Citations
“…These findings indicate that the participants wish to sound more native-like when speaking English. The results are consistent with the findings of Scales et al (2006) study. They found that the majority of the non-native speakers in their study stated that they tried to sound native-like.…”
Section: Questionnaire and Interview: Target Language Vs Mother Tongsupporting
confidence: 83%
“…In their study of the perceptions and attitudes of a group of 37 learners of English and 10 native American English speakers towards different accents of English (American, British, Chinese and Mexican), Scales et al (2006) found that over half of the participants preferred to sound like a native speaker although the majority were not able to identify the recordings of the accents presented to them. Scales et al (2006) conclude that accent is supposed to receive more consideration in language teaching.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have since then looked at various ways of ranking pronunciation targets. Scales et al, for example looked at learners' preferences, and found that learners preferred more intelligible accents (Scales et al 2006). Others (unsurprisingly) have also found that listeners prefer speech that is intelligible to them (Burda and Hageman 2005;Kennedy and Trofimovich 2008;Munro and Derwing 1995;Volberg et al 2006).…”
Section: Learnability Of Pronunciationmentioning
confidence: 99%
“…Karen Earline Schairer (1992) native speaker reaction to non native speech; Vivian Cook (1999) studied the appropriateness of the models in language use set by the native users ina mixed classroom; Marnie Reed's research of year 2000 examines the occurrence of hesitation in spontaneous speech of native and non native speakers; Roy C. Major et al (2002) examined the effects of non native accents on listening comprehension and stuied their implications for ESL assessment; Mary Grantham O'Brien (2004) enumerated upon the significance of pronunciation in an article aptly titles 'Pronunciation Matters';John M. Levis (2005) studied the changing contexts and shifting paradigms in pronunciation teaching; Nico C. Sifakis and Areti Maria Sougari (2005) studied the teachers' viewpoint on pronunciation specific issues and the possible links between pronunciation teaching, English as an international language, and the socio cultural identity of non native speakers of English. The 'native speaker myth' was studied by Paula Golombek and Stefanie Rehn Jordan (2005) studied the aspects of intelligibility and identity; A variety of English accents were the subject of the study carried out by Julie Scales et al (2006) where they studied the language learners' perception of accent; Deyuan He and Qunying Zhang (2010) worked on native speaker norms and China English, from the perspective of learners and teachers in China.…”
Section: Literature Reviewmentioning
confidence: 99%